Perbandingan Pertumbuhan Pagoda antara Larutan Nutrisi AB Mix dan Pupuk Organik Cair pada Sistem Hidroponik NFT - Yulianti, Fitri (Agropross : National Conference Proceedings of Agriculture, 2022)
Pagoda is a leaf vegetable plant that has a unique shape when compared to other types of mustard greens because the shape of this pagoda mustard is similar to a blooming flower, oval leaf shape with a very striking dark green colour, short-lived and has many nutrients and benefits. Vegetable cultivation technique using a hydroponic system that is often used is NFT (Nutrient Film Technology) because the design is quite simple to use. An important factor that must be considered in a hydroponic system to obtain optimal plant growth results is the need for nutrients. AB mix nutrition is a chemical fertilizer which is one of the standard nutrients used in hydroponic systems. The use of Liquid Organic Fertilizer (LOF) is expected to be an alternative hydroponic nutrient solution so that the vegetables produced are healthier, or what we are familiar with organic vegetables. The aim of the study was to compare the growth of pagoda plants against two types of nutrient solutions (AB mix and LOF) in the NFT hydroponic system. The research was carried out from March to April 2019 at Greenhouse, East Jakarta. The experimental design used was a completely randomized design. The treatment was the type of nutrient solution (AB mix and LOF) and was repeated 3 times. Observational data were analysed using t-test at 5% significance level. The results showed that pagoda growth in AB mix treatment was better than LOF so that LOF had not been able to become an alternative to AB mix for hydroponic nutrient solution for pagoda plants.